Synchronously oriented Fe microfiber & flake carbonyl iron/epoxy composites with improved microwave absorption and lightweight feature. (10th November 2019) - Nan, Hanyi; Qing, Yuchang; Gao, Hui; Jia, Hongyao; Luo, Fa; Zhou, Wancheng
Abstract: In this study, Fe microfibers (FMF) with a low percolation threshold and flake carbonyl iron (FCI) particles with high complex permeability were filled in an epoxy matrix, and shear force was applied to obtain synchronously oriented microstructures. The effect of the contents of FMF and/or FCI particles on the electromagnetic and microwave-absorbing properties of these composites was investigated in the frequency range of 2–18 GHz. Compared with single component-filled composites, the mixture of FMF and FCI imparted both suitable complex permittivity and enhanced complex permeability to the composite materials. Interestingly, the electromagnetic parameters of the composites could be tailored via simply regulating the ratio of FMF to FCI; thin and light microwave absorbers operating in the broadband range were obtained under the state of low content because of the synergy between the two components and the synchronous orientation of the fillers. An effective absorption of frequencies ranging from 3.5 to 18 GHz with reflection loss < −8 dB was achieved at thicknesses ranging from 1.0 to 2.0 mm.